Tasty rewards for ants: differences in elaiosome and seed metabolite profiles are consistent across species and reflect taxonomic relatedness - Konečná, Marie; Moos, Martin; Zahradníčková, Helena; Šimek, Petr; Lepš, Jan (Oecologia, 2018)
Diaspores of myrmecochorous plants consist of a seed (or fruit) and an attached appendage (elaiosome) which attracts ants. The elaiosome is a food resource for ants, whereas the seed is an energy source for subsequent germination and plant establishment. Although myrmecochory occurs in many phylogenetically unrelated lineages, multiple phylogenetic lineages display similar variation in elaiosome and seed metabolite composition due to convergent evolution. We focused on four families (Amaryllidaceae, Boraginaceae, Papaveraceae and Poaceae) each represented by two species from different genera. Diaspores of three populations per species were sampled and concentrations of 60 metabolites from five groups (amino acids, fatty acids, organic acids, polyols and sugars) were determined for both elaiosomes and seeds. Variability in metabolite composition was decomposed by hierarchical ANOVA and variation partitioning using redundancy analysis (reflecting both species nested within families, crossed with seed vs. elaiosome). Differences in the metabolite composition of elaiosomes and seeds were consistent across multiple phylogenetic origins (with more pronounced differences at the level of individual metabolites than at the level of metabolite groups) and supported the idea of convergent evolution under strong selection pressure. Elaiosomes contained higher amounts of easily digestible metabolites (especially amino acids) than seeds. Fatty acids were not more concentrated in elaiosomes, which contradicts the literal translation of "elaiosome" (= oil body). The differentiation of metabolite composition closely reflected taxonomic relatedness, particularly at the family level. Differences among populations within species were small, so the metabolite composition can thus be considered as a trait with relatively low intraspecific variability.
Keywords: Animals; Seeds; Germination; Convergent evolution; Myrmecochory; Ants; Variation partitioning; Phylogeny; klíčení; Reward; zvířata; fylogeneze; Ant–plant mutualism; odměna; Seed dispersal; semena rostlinná; Formicidae